Artificial intelligence and decoloniality: Insurgent arrangements and the question concerning cosmotechnics - Aguiar, Carlos Eduardo Souza; da Silva, Dayana Karla Melo (C-DISC, 2024)
This article examines the intersections between technology and coloniality, with a particular focus on the role of artificial intelligence (AI) in perpetuating colonial power structures and reinforcing exclusions. The study examines the ways in which historically marginalized groups—including Black people, the poor, women, Indigenous peoples, queer individuals, and those from peripheral areas—are reinterpreting AI, transforming it into a tool of resistance against the oppressive logics of Eurocentric modernity. The methodology is based on a qualitative approach, comprising interviews, an analysis of audiovisual materials, digital platforms, and social media. The research identified initiatives that propose technological alternatives based on diverse epistemological and ontological frameworks, thereby challenging the dominance of modern/colonial technological paradigms. The analysis of the data revealed that these groups adopt collaborative methodologies, with a particular focus on the inclusion of marginalized populations and the creation of new technological epistemologies. The findings demonstrate that these communities are developing technological arrangements based on non-Western cosmologies, thereby challenging Western dominance in technology. These practices not only adapt existing technologies but also create new forms of technological interaction that reflect their specific realities and contexts. The study concludes that the decolonization of technology is both possible and necessary, with the adoption of cosmotechnics that respect cultural and epistemological diversity, paving the way for fairer, plural, and inclusive technological futures.